The Science, Economics, and Politics of Global Climate Change: A Review of The Climate Casino by William Nordhaus - Jaffe, Adam B.; Kerr, Suzi (Journal of Economic Literature, 2015)
The problem of global climate change presents overwhelming factual, analytical, and normative challenges. Nordhaus surveys this terrain bravely and mostly successfully. He explains the scientific/economic consensus that the planet is warming, that people are responsible, that the consequences are bad, and that immediate action is benefit/ cost justified. He also discusses the efficient policy response, and the challenges of achieving coordinated global action. His approach is mostly that of standard neoclassical economics, and some of the limitations of that paradigm in this context are not addressed. But overall, The Climate Casino provides an excellent self-contained introduction to the subject. (JEL D61, H23, Q51, Q54, Q58, D72)